Earnings Management Behaviour: The Role of Pressure on Behaviour Performance - Septiari, Dovi; Maruli, Matheus (Asian Journal of Business and Accounting, 2017)
Manuscript type: Research paper. Research aims: This study aims to examine the impact of pressure on behaviour performance in the context of earnings management. Three specific key points were tested: whether pressure affects earnings management behaviour; whether pressure has an interaction effect with ethical orientation on earnings management and whether pressure has an interaction effect with professional commitment on earnings management behaviour. Design/ Methodology/ Approach: This study employs a laboratory experiment which involves 102 undergraduate students as samples. The independent variable, pressure, is manipulated as follows: (1) no pressure is given and (2) pressure is given. The other two independent variables are ethical orientation and professional commitment which are measured by using the 5-point Likert scale. The dependent variable, earnings management behaviour, is measured by using the 7- point Likert scale. Research findings: The results reveal that there is a relationship between individual ethical orientation and earnings management behaviour. The results also find that participants with a higher level of professional commitment are less likely to engage in earnings management. Moreover, it is observed that pressure has an effect on earnings management behaviour. In particular, there is an interaction effect between pressure and earnings management factors such as ethical orientation and professional commitment. Theoretical contribution/ Originality: By investigating the effect of pressure on earnings management behaviour and by examining the interaction effect between pressure and ethical orientation and professional commitment, this study adds to current literature. While prior studies examined the elements of pressure causing individuals to engage in earnings management behaviour, this study examines whether pressure, in the form of legal consequences and written justifications, could potentially reduce earnings management behaviour. Practitioner/ Policy implication: The results of this study are beneficial to the management of organisations in recognising factors that may influence managers to perform earnings management. The results of this study can alert policy makers on the use of pressure, which comes in the form of legal consequences and written justifications, for minimising earnings management behaviour. Finally, the outcome of this study also benefits academicians such that they may want to consider reviewing other ethical orientations and professional commitment components in their accounting syllabi so as to increase ethics and professionalism among accounting students. Research limitation: The participants of this research are students who had limited working experiences. Keywords: Earnings Management Behaviour, Ethical Orientation, Pressure, Professional Commitment. JEL Classification: M41